2021
DOI: 10.1093/rheumatology/keab724
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of cardiac impairment favored by two-dimensional speckle tracking echocardiology in patients with systemic sclerosis

Abstract: Background Cardiac involvement is a major cause of death in systemic sclerosis (SSc), while early detection remains a challenge. Objectives The purpose of this study was to investigate the prevalence and clinical implications of cardiac impairment in SSc. Methods 95 consecutive SSc patients (55.6 ± 13.8 years old, 5.3 ± 8.1 years from diagnosis) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 39 ] 2020 47 SSc patients vs 36 healthy controls CRP, Galectin-3 CRP and Galectin-3 correlated with PSS Jiang, et al . [ 40 ] 2022 95 SSc patients CRP CRP associated with reduced GLS Rodriguez-Reyna, et al . [ 42 ] 2015 62 SSc patients CRP CRP associated with myocardial fibrosis on cMRI Gieszczyk, et al .…”
Section: Cardiac Troponins: Marker Of Cardiac Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 39 ] 2020 47 SSc patients vs 36 healthy controls CRP, Galectin-3 CRP and Galectin-3 correlated with PSS Jiang, et al . [ 40 ] 2022 95 SSc patients CRP CRP associated with reduced GLS Rodriguez-Reyna, et al . [ 42 ] 2015 62 SSc patients CRP CRP associated with myocardial fibrosis on cMRI Gieszczyk, et al .…”
Section: Cardiac Troponins: Marker Of Cardiac Injurymentioning
confidence: 99%
“…Studies have shown a correlation between CRP and ventricular impairment measured through echocardiographic longitudinal strain, which is a more sensitive marker of left ventricular dysfunction before overt reduction in LVEF. [ 39 , 40 ] Studies looking at myocardial inflammation and fibrosis using cMRI have similarly demonstrated a correlation with CRP levels. [ 41 , 42 ] Higher levels of CRP are associated with reduced 5-year survival in SSc patients, particularly with interstitial lung disease (ILD).…”
Section: Pro-inflammatory Cytokines: Marker Of Inflammationmentioning
confidence: 99%